Functionalization of Management Elements in Managing Thriving Education Units in Madrasah Aliyah - Herman Herman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The head of the madrasah as a top manager and leader has the obligation and responsibility to functionalize the elements of management in managing the education unit. The purpose of this study was to find out how to functionalize the elements of management in managing the thriving education unit at MAN 1 West Aceh. This study uses a descriptive qualitative analysis approach in revealing factual conditions related to ways of functionalizing the elements of management in managing a thriving education unit. The method of collecting data is through observation, interviews, and document studies on reports on madrasah activities. Data processing techniques by means of data verification, data presentation, data reduction, and drawing conclusions from research results. The technique of analyzing research data is by reflecting, interpreting and planning actions on the research results. The results show that MAN 1 West Aceh has been classified as good in terms of how to functionalize management elements in managing educational units, including: 1) functionalizing elements of human resources (man), by planning human resource needs, developing human resources and managing human resources, 2) functionalizing the financial element (money) by following the budget preparation procedures, using the budget, monitoring and reporting the budget, 3) functionalizing the elements of facilities and infrastructure (materials) by planning educational facilities and infrastructure, utilizing educational facilities and infrastructure and supervising educational facilities and infrastructure as well as 4) functionalizing the education marketing element by marketing educational service products, promoting educational services and marketing the educational service process.